Triassic Basin Stratigraphy at Grand Manan, New Brunswick, Canada - McHone, J. (Atlantic Geology, 2011)
ABSTRACT The island of Grand Manan (Canada) in the southwestern Bay of Fundy has the only exposed strata and basalt of the Grand Manan Basin, a mainly submerged Early Mesozoic riﬅ basin about 30 km wide by 70 km long. The basin is bounded on the southeast by the west-dipping Red Point Fault, which bisects the island, and on the northwest by a submarine border fault marked by the Murr Escarpment, a bathymetric feature that parallels the coast of Maine (USA). A fault-bounded horst of Ediacaran to Cambrian rocks separates the Grand Manan Basin from the much larger Fundy Basin to the east. The Ashburton Head, Seven Days Work, and Southwest Head members of the end-Triassic Dark Harbour Basalt cover most of western Grand Manan with a total thickness around 240 m. Up to 12 m of sub-horizontal grey mudstone and fine-grained red sandstone of the Dwellys Cove Formation are exposed along the western shoreline beneath the basalt. Coarse red arkosic sandstone a few metres thick at Miller Pond Road rests on a basement of Late Ediacaran rocks east of the basin. Exposures of the Dwellys Cove and Miller Pond Road formations are at the top and bottom, respectively, of several km (?) of sub-horizontal Late Triassic clastic basin strata, juxtaposed by the eastern border fault. Extending from beneath the Miller Pond Road sandstone, a level surface of low relief forms much of the eastern island and its archipelago, which may be interpreted as a relict Late Triassic peneplain that was beneath the Mesozoic strata.